The Failure of Indonesia’s Public Diplomacy in Managing Malaysian Cultural Claim Issue - Iva Rachmawati; Sri Issundari (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2010)
According to traditional conception of public diplomacy, the positive building of country’s image is the main aim of public diplomacy by sharing clear and credible information and persuading other foreign government and public abroad. In the era of rapid development of information and communication technology, the good image of one country cannot be build by focusing on the parties abroad. The image should be built by focusing on domestic public. By sharing clear and credible information government can persuade public in shaping supportive attitudes. Unfortunately, Indonesia government failed in managing public diplomacy. The anarchic actions and narrative coercion were frequently happened during Malaysian cultural claims. These were unsupportive situation for Indonesian image itself. Lack of mechanism in public access to obtain trusted information and also lack of guidance to respond sensitive issues determine those attitude and lessen the level of relation between countries.